Variability of CubeQuant T1rho, Quantitative DESS T2, and Cones Sodium MRI in Knee Cartilage - Jordan, Caroline D. (2014)
OBJECTIVE: To measure the variability of T(1ρ) relaxation times using CubeQuant, T(2) relaxation times using quantitative double echo in steady state (DESS), and normalized sodium signals using 3D cones sodium MRI of knee cartilage in vivo at 3T. DESIGN: Eight healthy subjects were scanned at 3T at baseline, one day, five months, and one year. Ten regions of interest (ROIs) of knee cartilage were segmented in the medial and lateral compartments of each subject’s knee. T(1ρ) and T(2) relaxation times and normalized sodium signals were measured and the root-mean-square coefficient of variation (CV(RMS)) was calculated. Intra-subject variability was measured over short, moderate and long-term, as well as intra-observer and inter-observer variability. RESULTS: The average intra-subject CV(RMS) measurements over short, moderate, and long-term time periods were 4.6%, 6.1%, and 6.0% for the T(1ρ) measurements, 6.4%, 9.3%, and 10.7% for the T(2) measurements and 11.3%, 11.6%, and 12.9% for the sodium measurements, respectively. The average CV(RMS) measurements for intra-observer and inter-observer segmentation were 3.8% and 5.7% for the T(1ρ) measurements, 4.7% and 6.7% for the T(2) measurements, and 8.1% and 11.4% for the sodium measurements, respectively. CONCLUSIONS: These CV(RMS) measurements are substantially lower than previously measured changes expected in patients with advanced osteoarthritis compared to healthy volunteers, suggesting that CubeQuant T(1ρ), quantitative DESS T(2) and 3D cones sodium measurements are sufficiently sensitive for in vivo cartilage studies.